Optimization of green synthesized silver nanoparticles from ananas comosus peel extract and its antioxidant activity / Nurul Raihan Mohd Radzi - Mohd Radzi, Nurul Raihan (2020)
At present, biosynthesis approach by using waste materials from food is widely used as it is proven to be environmentally friendly and cost friendly to prepare metallic nanoparticles. This current study aims to synthesize, optimize as well as characterize the biosynthesized silver nanoparticles (AgNPs) and identify their antioxidant activities using the outer peel extracts of the pineapple (Ananas comosus), which is a food waste material. The optimization of different temperature (70◦C, 80◦C and 90◦C)as well as different pH (pH 7, pH 8 and pH 9) was done. All the synthesized and optimized AgNPs samples were characterized by UV-Visible Spectroscopy (200 and800 nm). The antioxidant activities of the AgNPs were identified using free radical scavenging ability on 2,2-diphenyl-2-picrylhydrazyl (DPPH) and total phenolic content (TPC). The outcome of this study showed colour changes from colour less to red dish dark brown that indicate the formation of AgNPs. Treatment at pH 9 and temperature of 90◦C showed the optimum treatment as both changes colour to dark brown faster after 24 hours of incubation compared to other treatments. The results were found that at pH 9, the surface plasmon resonance peak for biosynthesized AgNPs was at 425 nm on Day 2 while other treatment took longer time to exhibit the peak. Biosynthesized AgNPs treated at temperature 90◦C showed the optimum temperature when it exhibited peak at 420 nm on Day 3. The biosynthesized of AgNPs from pineapple peel extracts exhibited potential antioxidant activity in the DPPH scavenging and the TPC assay. The highest DPPH scavenging percentage is at84.75% for AgNPs treated at pH 9 and 80.29 % for AgNPs treated at 90◦C with concentration of 1000 μg/mL. Meanwhile AgNPs showed second highest phenolic content when compared to pineapple peel extracts alone which are at 338 μg GAE/gfor pH 9 and 318 μg GAE/g for temperature of 90◦C. Thus, the best treatment to synthesis and exhibit antioxidant potential of AgNPs from pineapple peel extract was at pH 9.